THE ROLE OF CUSTOMER SATISFACTION MEDIATES SERVICE QUALITY ON CUSTOMER LOYALTY - Ni Kadek Yudani; Ni Nyoman Kerti Yasa (Adisam Publisher, 2024)
Customer loyalty is essential for a company as a form of success. Customer loyalty arises from customer satisfaction with service quality. This research intends to dissect the impact of customer satisfaction when mediating service quality on customer loyalty. The location of this research is Denpasar City, with a sample of 110 respondents who have used the Agoda online travel application at least a couple of times utilizing purposive sampling methodology, and conveyed utilizing a Google Form questionnaire, measuring 11 indicators using a Likert Scale. Data analysis technique applied is outer model analysis, inner model and hypothesis testing. The aftereffects of this exploration show that all hypotheses are accepted. Service quality affects customer satisfaction, service quality affects customer loyalty, customer satisfaction meaningfully affects customer loyalty, service quality affects customer loyalty with the intervention of customer satisfaction, and from the results of this research it can be understood that customer satisfaction is mediating variable for the influence of service quality on customer loyalty. In order to increase customer loyalty, this can be done by improving service quality and customer satisfaction.